Green and environment-friendly leather softening method
By using a combination of a mixture of sodium bicarbonate and magnesium sulfate, a composite enzyme preparation and a bio-based emulsion in leather processing, the problem of using harmful chemicals in traditional leather softening processes is solved, and green and environmentally friendly leather softening and high-quality leather finished products are achieved.
Patent Information
- Application Number
- CN202411967738.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Traditional leather softening processes rely on harmful chemicals, which lead to environmental pollution and health risks. At the same time, it is difficult to accurately control the softening effect, resulting in poor leather quality.
The mixture of sodium bicarbonate and magnesium sulfate is pretreated, softened with a composite enzyme preparation, and is polished by a bio-based emulsion to achieve green and environmentally friendly leather softening.
It effectively abandons harmful chemicals in traditional leather softening processes, significantly reduces environmental pollution, improves the softness, tensile strength and breathability of the leather, while ensuring the natural characteristics and environmental protection of the leather.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of leather processing, in particular to a green and environmentally friendly leather softening method. Background Art
[0002] With the acceleration of global industrialization and the continuous increase in consumer demand for leather products, the leather industry has long occupied an important position in the manufacturing industry. However, the traditional leather softening process is highly dependent on chemical agents. In the routine operation process, chemical substances such as chrome tanning agent, formaldehyde and various chlorinated organic solvents are used on a large scale. Although chrome tanning agent can improve the stability and durability of leather to a certain extent, the heavy metal chromium ions therein are extremely bioaccumulative and toxic. If they are discharged indiscriminately during the leather processing link, they will cause immeasurable and almost irreversible serious pollution to the soil and water ecosystems, causing the surrounding ecological environment to be devastated and biodiversity to decline sharply. Formaldehyde, as a common softening agent, not only has a pungent smell, but its volatility will continue to erode the respiratory tract and lung tissues of workshop operators. Long-term exposure can easily induce serious health problems such as respiratory diseases and cancer. At the same time, the formaldehyde remaining in leather products will also pose a potential threat to consumers' skin and body functions. Chlorinated organic solvents are very easy to evaporate into the atmosphere during the processing process, participating in photochemical reactions to generate highly toxic substances such as dioxins, posing a threat to the life, health and safety of surrounding residents.
[0003] In addition, traditional softening methods also have many disadvantages and shortcomings. For example, it is difficult to accurately control the degree of hydrolysis of the leather fiber structure, which often leads to uneven leather softening effects, local excessive softening resulting in damage to fiber strength and greatly reduced durability of the product, or insufficient softening resulting in quality defects such as stiff leather feel and poor flexibility. The disordered penetration and residue of chemical agents will also interfere with the original orderly arrangement structure of the leather fibers, destroying its inherent natural texture, resulting in the finished product being far from meeting the increasingly stringent quality demands of current consumers in terms of key performance indicators such as color, touch and breathability.
[0004] Therefore, according to the above-mentioned related technologies, it is urgent to develop a green and environmentally friendly leather softening method. Summary of the invention
[0005] In view of this, the purpose of the present invention is to propose a green and environmentally friendly leather softening method, which abandons traditional harmful chemicals, utilizes natural biological materials and mild physical means, achieves efficient softening while ensuring the natural characteristics and environmental friendliness of the leather.
[0006] Based on the above purpose, the present invention provides a green and environmentally friendly leather softening method.
[0007] A green and environmentally friendly leather softening method comprises the following steps:
[0008] Step S1. Pretreatment: pretreating the leather with reagent A to obtain a crude leather product 1;
[0009] Step S2. Softening: Softening the crude leather product 1 with reagent B to obtain the crude leather product 2;
[0010] Step S3. Finishing: using reagent C to finish the leather crude product 2 to obtain a leather finished product;
[0011] In step S1, the reagent A is a mixed solution of sodium bicarbonate and magnesium sulfate;
[0012] The reagent B in step S2 is a complex enzyme preparation;
[0013] The composite enzyme preparation is obtained by mixing collagen hydrolase, plant-derived protease and metal organic framework enzyme-carrying microparticles;
[0014] The reagent C in step S3 is a bio-based emulsion.
[0015] Preferably, the pre-processing process in step S1 is as follows:
[0016] Place the raw hide in a 25-30℃ warm water bath and stir for 30 minutes to wash away impurities and blood on the surface of the raw hide. Then, place it in a 20kHz, 400W ultrasonic oscillation for 15 minutes to remove impurities and open pores. Then, place it in a 2.45GHz, 600W microwave cavity for 10 minutes to accelerate the temperature rise and promote fiber expansion, laying the foundation for softening. After draining, use reagent A to adjust the pH to 7.5-8 to neutralize the natural acid, activate the subsequent reaction, create a suitable charge and osmotic pressure environment for the enzyme molecules, and promote subsequent efficient attachment and penetration. This gentle treatment can avoid damage to the leather structure.
[0017] The usage ratio of the raw hide to water is 10-12 g:100-110 mL.
[0018] Preferably, the preparation process of reagent A in step S1 is as follows:
[0019] Mixing a 1% sodium bicarbonate solution, a 0.5% glucose solution and a 0.3% magnesium sulfate solution to obtain reagent A;
[0020] The volume ratio of the sodium bicarbonate solution, the glucose solution and the magnesium sulfate solution is 55-58:28-30:12-16.
[0021] Preferably, the softening process in step S2 is as follows:
[0022] The crude leather product 1 is immersed in a buffer solution containing 3%-3.5% reagent B, and shaken at 40-45°C, pH=7-7.5, and 80-100 rpm for 2-3 hours, with precise temperature control to maintain enzyme activity and shaking to promote uniform enzyme contact;
[0023] The bath ratio during softening in step S2 is 1:8-9, and the buffer solution is disodium hydrogen phosphate-citric acid.
[0024] Preferably, the preparation process of the collagenase in the reagent B is as follows:
[0025] The pig gastric mucosal tissue is washed, and impurities such as fat and blood on the surface are removed and the tissue is cut into small pieces. The pre-treated gastric mucosal tissue is placed in an extraction buffer. At 4-10°C, the tissue is homogenized with a homogenizer to break the cells and release the enzyme. The homogenate is then stirred and extracted at 4-10°C for 4-6 hours to allow the collagenase to be fully dissolved in the extraction buffer. The extracted homogenate is then centrifuged at a speed of 4000-6000rpm for 20-30min to remove tissue residues and insoluble matter to obtain a supernatant containing the collagenase. Solid ammonium sulfate is added to the obtained supernatant to make the saturation of the ammonium sulfate reach 40%-60%, and the supernatant is allowed to stand at 4°C for 2-4 hours to precipitate the collagenase. The precipitate is then collected by centrifugation to obtain the collagenase.
[0026] The extraction buffer is a phosphate-hydrochloric acid buffer with a pH of 7.0-7.5 and containing 0.1-0.5M NaCl;
[0027] The volume ratio of the extraction buffer to the gastric mucosal tissue block is 8-10:1-2.
[0028] Preferably, the preparation process of the plant-derived protease in the reagent B in step S2 is as follows:
[0029] Step S2011. Picking ripe and fresh papaya, removing the dirt, impurities and soft and rotten parts on the surface, washing with clean water and draining, peeling and core-removing the papaya, cutting into small pieces, and freezing the cut papaya pieces in liquid nitrogen for 30-60 minutes. This step can instantly freeze the papaya cells, destroy the cell structure, facilitate the release of subsequent enzymes, and help reduce the activity loss of the enzymes before extraction. The frozen papaya pieces are placed in a vacuum freeze dryer and dried for 24-48 hours at -50°C-40°C and a vacuum degree of about 0.06-0.08MPa, until the material is completely dehydrated and becomes a loose and fragile dry block, which is convenient for subsequent grinding into powder;
[0030] Step S2012. Add the dried papaya powder to a Tris-HCl buffer solution with a pH of 7.5-8.0 at a ratio of 1 g: 5-10 mL, place it in a low temperature environment of 4°C, slowly stir it on a magnetic stirrer for 4-6 hours to ensure that the enzyme protein is fully dissolved in the buffer solution, transfer the extract to a high-speed refrigerated centrifuge, centrifuge it at 4°C and 10,000-12,000 rpm for 20-30 minutes, separate the supernatant, add ammonium sulfate powder to the supernatant, stir it while adding, and gradually increase its saturation to 40%-60%, let it stand at 4°C for 2-4 hours to promote the precipitation of elastase, and then centrifuge it again at a speed of 10,000-12,000 rpm and a temperature of 4°C for 20-30 minutes, collect the precipitate, and obtain the plant-derived protease;
[0031] In step S2012, 0.1-0.2 M NaCl and 0.01-0.02 M EDTA are added to the Tris-HCl buffer, wherein 0.1-0.2 M NaCl is used to maintain a suitable ionic strength to promote the dissolution of the enzyme protein, and 0.01-0.02 M EDTA is used to chelate metal ions to prevent potential inhibition or interference of metal ions on enzyme activity.
[0032] Preferably, the preparation process of the metal organic framework enzyme-loaded microparticles in the reagent B in step S2 is as follows:
[0033] Step S2021. Dissolve zirconium chloride in N,N-dimethylformamide, stir at room temperature for 1-2 hours, and prepare a zirconium chloride solution with a concentration of 0.08-0.1M;
[0034] Step S2022. Dissolve terephthalic acid in N,N-dimethylformamide, stir at room temperature for 1-2 hours, and prepare a terephthalic acid solution with a concentration of 0.08-0.1M;
[0035] Step S2023. The zirconium chloride solution and the terephthalic acid solution are mixed in a polytetrafluoroethylene-lined reactor at a molar ratio of 1:1, and acetic acid is added as a regulator to control the growth rate and particle size of MOF. After the reactor is sealed, it is placed in an oven and reacted at 100-120° C. for 10-12 hours. During the reaction, the metal ions and the organic ligands undergo coordination reaction in a high temperature and high pressure solvent environment to obtain MOF particles with a particle size of 2-5 nm;
[0036] Step S2024. The MOF particles are dispersed in a toluene solution, 3-aminopropyltriethoxysilane is added, and the reaction is stirred at 70-80° C. for 6-12 hours under nitrogen protection to modify the surface of the MOF particles to enhance the binding ability of the MOF particles with the enzyme. After the reaction is completed, the surface-modified MOF particles are collected by centrifugation, washed three times with toluene and ethanol respectively to remove the unreacted silane coupling agent, and then dried in a vacuum drying oven to obtain functionalized MOF particles;
[0037] Step S2025. Dissolve the collagen hydrolase and the plant-derived protease in a phosphate buffer solution at pH 7-8, add the functionalized MOF microparticles, and stir the reaction at room temperature for 12-24 hours to load the enzyme onto the MOF microparticles by physical adsorption or chemical bonding (such as the formation of an amide bond between the amino group of the enzyme and the carboxyl group on the surface of the MOF), thereby obtaining metal organic framework enzyme-loaded microparticles;
[0038] Step S2026. Mix 10-15 g of collagen hydrolase, 10-12 g of plant-derived protease and 18-22 g of metal organic framework enzyme-loaded microparticles to obtain reagent B.
[0039] The molar ratio of acetic acid to zirconium chloride in step S2023 is 1.5-2:1.
[0040] The mass ratio of 3-aminopropyltriethoxysilane to MOF particles in step S2024 is 8-10:100.
[0041] The mass ratio of the collagen hydrolase, the plant-derived protease and the functionalized MOF microparticles in step S2025 is 2-3:2-2.5:30-35.
[0042] The mass ratio of the collagen hydrolase, the plant-derived protease and the metal organic framework enzyme-loaded microparticles in step S2026 is 10-15:10-12:18-22.
[0043] Preferably, the retouching process in step S3 is as follows:
[0044] The leather crude product 2 is bombarded with nitrogen plasma at 50W for 3 minutes to improve the surface activity and make the grafted emulsion stronger. Then, it is placed in an emulsion containing 8%-10% of reagent C, with a bath ratio of 1:6-8, and tanned at 50-55°C for 80-90 minutes. Warmth helps the oil to penetrate and the tanning is evenly distributed. Then, it is cured at 45-50°C for 20 minutes to make the film dense, bright and lasting in color. The emulsion particle size is 80-120nm, stably dispersed, and formed into a nano film after spraying, which gives the leather waterproof, breathable and antibacterial functions, and the source is fully biodegradable and has no ecological burden.
[0045] The content of the emulsifier in the emulsion is 0.5%-0.6%.
[0046] Preferably, the preparation process of the bio-based emulsion in step S3 is as follows:
[0047] Step S301. Place the phytosterol with a purity of 95%-98% in a vacuum oven and dry it for 2-3 hours at 50-60°C and a vacuum degree of 0.08-0.09 MPa to remove moisture and a small amount of volatile impurities. Grind the dried phytosterol into fine powder and pass it through an 80-100 mesh sieve to better disperse it in the reaction system to obtain phytosterol;
[0048] Step S302. Select chitosan with a deacetylation degree of 80%-90% and a molecular weight of 60-80kDa, use glycidyl trimethyl ammonium chloride as a quaternizing agent, disperse the chitosan in an isopropanol-water mixed solvent, add sodium hydroxide to adjust the pH to 10-11, slowly drop a 20%-30% glycidyl trimethyl ammonium chloride solution, stir and react at 60-70°C for 6-8h, after the reaction is completed, wash with ethanol 3 times to remove unreacted reagents and salts to obtain chitosan quaternary ammonium salt, dissolve the prepared chitosan quaternary ammonium salt in deionized water to prepare a solution with a mass fraction of 5%-10%, filter through a 0.22-0.45μm filter membrane before use to remove possible insoluble impurities to obtain a chitosan quaternary ammonium salt solution;
[0049] Step S303. Soaking wood pulp in a buffer solution containing TEMPO, sodium bromide and sodium hypochlorite, reacting at room temperature in the dark for 2-3 hours, stirring continuously during the reaction, washing with deionized water to neutrality after the reaction, obtaining oxidized cellulose with carboxyl groups on the surface, and then dispersing the oxidized cellulose in water, using an ultrasonic cell disruptor at a power of 400-600W for 30-60min to depolymerize the cellulose into nanometer size, obtaining an amphiphilic nanocellulose suspension, wherein the solid content is adjusted to 2%-3%, and centrifuging at a speed of 8000-10000rpm for 10-15min to remove large particle impurities that are not completely depolymerized, and obtaining an amphiphilic nanocellulose suspension;
[0050] Step S304. Add deionized water to a three-necked flask equipped with a mechanical stirrer, a thermometer and a condenser, heat it to 40-50°C, stir it at 300-400rpm, slowly drop the phytosterol powder, add an emulsifier, and continue stirring for 30-40min to form a primary emulsion of phytosterols, wherein the hydrophilic group of the emulsifier faces the water phase and the lipophilic group wraps the phytosterol particles so that they are initially dispersed in the water phase;
[0051] Step S305. Slowly drop the chitosan quaternary ammonium salt solution into the primary emulsion of phytosterols, and the dropping time is controlled at 20-30 minutes. During this period, the temperature is raised to 60-70°C, the stirring speed is increased to 500-600rpm, and the reaction is carried out for 1-2 hours, so that the chitosan quaternary ammonium salt and the phytosterols interact to a certain extent, such as electrostatic adsorption, hydrogen bonding, etc., to enhance the stability and functionality of the emulsion. Subsequently, the amphiphilic nanocellulose suspension is added dropwise to the reaction system. After the dropwise addition is completed, the stirring reaction is continued at 70-80°C for 2-3 hours to promote the uniform dispersion of the nanocellulose and further compound with other components in the emulsion to form a bio-based emulsion with a stable structure. The amphiphilicity of the nanocellulose enables it to interact with the chitosan quaternary ammonium salt in the aqueous phase and connect with the phytosterol particles through the hydrophobic region, playing the role of a bridge and reinforcing the structure.
[0052] The volume ratio of isopropanol to water in the isopropanol-water mixed solvent in step S302 is 1:1.
[0053] The pH of the buffer solution in step S303 is 10-10.5.
[0054] In step S304, the deionized water accounts for 40%-50% of the total mass of the emulsion.
[0055] In step S304, the emulsifier is Tween-80, and the amount of the emulsifier is 10%-20% of the mass of the phytosterols.
[0056] The mass ratio of the phytosterol, the chitosan quaternary ammonium salt solution and the amphiphilic nanocellulose is 3-5:80-85:2-3.
[0057] Beneficial effects of the present invention:
[0058] The present invention fundamentally abandons the use of a series of harmful chemicals such as chrome tanning agents, formaldehyde, etc. in the traditional leather softening process, greatly reduces the total amount of pollutants discharged into the environment during the leather production process, and completely eliminates heavy metal pollution and the generation of toxic volatile substances.
[0059] The present invention, by means of the ingenious design of the composite enzyme preparation and the unique efficacy of the bio-based emulsion, greatly improves the softness of the finished leather product, increases the tensile strength and tear strength, increases the air permeability, and improves the color uniformity and gloss durability, and has broad application prospects. DETAILED DESCRIPTION
[0060] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0061] Preparation Example 1: A method for preparing reagent A, comprising the following steps:
[0062] Reagent A was obtained by mixing 55 mL of 1% sodium bicarbonate solution, 28 mL of 0.5% glucose solution and 12 mL of 0.3% magnesium sulfate solution.
[0063] Preparation Example 2: A method for preparing reagent A, comprising the following steps:
[0064] Reagent A was obtained by mixing 56 mL of 1% sodium bicarbonate solution, 29 mL of 0.5% glucose solution and 14 mL of 0.3% magnesium sulfate solution.
[0065] Preparation Example 3: A method for preparing reagent A, comprising the following steps:
[0066] Reagent A was obtained by mixing 58 mL of 1% sodium bicarbonate solution, 30 mL of 0.5% glucose solution and 16 mL of 0.3% magnesium sulfate solution.
[0067] Preparation Example 4: A method for preparing reagent B, comprising the following steps:
[0068] S1. Wash the pig gastric mucosal tissue, remove the fat, blood and other impurities on the surface and cut it into small pieces. Put 10 mL of the pretreated gastric mucosal tissue into 80 mL of phosphate buffer solution with pH = 7.0 and containing 0.1 M NaCl. At 4°C, use a homogenizer to homogenize the tissue to break the cells and release the enzyme. Then, stir and extract the homogenate at 4°C for 4 hours to allow the collagenase to be fully dissolved in the extraction buffer. Then, centrifuge the extracted homogenate at 4000 rpm for 20 minutes to remove tissue residues and insoluble matter to obtain a supernatant containing collagenase. Add solid ammonium sulfate to the obtained supernatant to make the saturation of ammonium sulfate reach 40%. Let it stand at 4°C for 2 hours to precipitate the collagenase. Then, collect the precipitate by centrifugation to obtain collagenase.
[0069] S2. Pick ripe and fresh papaya, remove the dirt, impurities and soft and rotten parts on the surface, wash with clean water and drain, peel and core the papaya, cut into small pieces, and freeze the cut papaya pieces in liquid nitrogen for 30 minutes. This step can instantly freeze the papaya cells, destroy the cell structure, facilitate the release of subsequent enzymes, and help reduce the activity loss of enzymes before extraction. The frozen papaya pieces are placed in a vacuum freeze dryer and dried at -50°C and a vacuum degree of about 0.06MPa for 24 hours until the material is completely dehydrated and becomes a loose and fragile dry block, which is convenient for subsequent grinding into powder;
[0070] S3. Add 0.1M NaCl and 0.01M EDTA to a Tris-HCl buffer solution at pH = 7.5, wherein 0.1M NaCl is used to maintain a suitable ionic strength and promote the dissolution of the enzyme protein, and 0.01M EDTA is used to chelate metal ions to prevent potential inhibition or interference of metal ions on enzyme activity. Add the dried papaya powder to the Tris-HCl buffer solution at a ratio of 1g:5mL, place it in a low temperature environment of 4°C, and slowly stir it on a magnetic stirrer for 4h to ensure that the enzyme protein is fully dissolved in the buffer solution. Transfer the extract to a high-speed refrigerated centrifuge, centrifuge it at 4°C and 10000rpm for 20min, separate the supernatant, add ammonium sulfate powder to the supernatant, stir it while adding, and gradually increase its saturation to 40%, let it stand at 4°C for 2h to promote the precipitation of elastase, and then centrifuge it again at a speed of 10000rpm and a temperature of 4°C for 20min, collect the precipitate, and obtain a plant-derived protease;
[0071] S4. The zirconium chloride was dissolved in N,N-dimethylformamide and stirred at room temperature for 1h to prepare a zirconium chloride solution having a concentration of 0.08M;
[0072] S5. The terephthalic acid was dissolved in N, N-dimethylformamide and stirred at room temperature for 1 h to prepare a terephthalic acid solution having a concentration of 0.08 M;
[0073] S6. The zirconium chloride solution and the terephthalic acid solution are mixed in a polytetrafluoroethylene-lined reactor at a molar ratio of 1:1, and acetic acid is added as a regulator. The molar ratio of acetic acid to zirconium chloride is 1.5:1 to control the growth rate and particle size of MOF. After the reactor is sealed, it is placed in an oven and reacted at 100°C for 10 hours. During the reaction, the metal ions and the organic ligands undergo coordination reaction in a high temperature and high pressure solvent environment to obtain MOF particles with a particle size of 2 nm.
[0074] S7. The MOF particles were dispersed in a toluene solution, 3-aminopropyltriethoxysilane was added, and the mass ratio of 3-aminopropyltriethoxysilane to MOF particles was 8:100. The mixture was stirred and reacted at 70°C for 6 hours under nitrogen protection to modify the surface of the MOF particles so as to enhance the binding ability of the MOF particles with the enzyme. After the reaction, the surface-modified MOF particles were collected by centrifugation, washed three times with toluene and ethanol respectively to remove the unreacted silane coupling agent, and then dried in a vacuum drying oven to obtain functionalized MOF particles.
[0075] S8. Dissolve 20 g of collagen hydrolase and 20 g of plant-derived protease in a phosphate buffer solution at pH = 7, add 300 g of functionalized MOF microparticles, and stir the reaction at room temperature for 12 h to load the enzyme onto the MOF microparticles by physical adsorption or chemical bonding (such as the formation of an amide bond between the amino group of the enzyme and the carboxyl group on the surface of the MOF), to obtain metal organic framework enzyme-loaded microparticles;
[0076] S9. Mix 10 g of collagen hydrolase, 10 g of plant-derived protease and 18 g of metal organic framework enzyme-loaded microparticles to obtain reagent B.
[0077] Preparation Example 5: A method for preparing reagent B, comprising the following steps:
[0078] S1. Wash the pig gastric mucosal tissue, remove the fat, blood and other impurities on the surface and cut it into small pieces. Put 15 mL of the pretreated gastric mucosal tissue into 90 mL of phosphate buffer solution with pH = 7.3 and containing 0.3M NaCl. Use a homogenizer to homogenize the tissue at 6°C to break the cells and release the enzyme. Then, stir and extract the homogenate at 6°C for 5 hours to allow the collagenase to be fully dissolved in the extraction buffer. Then, centrifuge the extracted homogenate at 5000 rpm for 25 minutes to remove tissue residues and insoluble matter to obtain a supernatant containing collagenase. Add solid ammonium sulfate to the obtained supernatant to make the saturation of ammonium sulfate reach 50%. Let it stand at 4°C for 3 hours to precipitate the collagenase. Then, collect the precipitate by centrifugation to obtain collagenase.
[0079] S2. Pick ripe and fresh papaya, remove the dirt, impurities and soft and rotten parts on the surface, wash with clean water and drain, peel and core the papaya, cut into small pieces, and freeze the cut papaya pieces in liquid nitrogen for 50 minutes. This step can instantly freeze the papaya cells, destroy the cell structure, facilitate the release of subsequent enzymes, and help reduce the activity loss of enzymes before extraction. The frozen papaya pieces are placed in a vacuum freeze dryer and dried at -45°C and a vacuum degree of about 0.07MPa for 36 hours until the material is completely dehydrated and becomes a loose and fragile dry block, which is convenient for subsequent grinding into powder;
[0080] S3. Add 0.15M NaCl and 0.015M EDTA to a Tris-HCl buffer solution at pH = 7.8, wherein 0.15M NaCl is used to maintain a suitable ionic strength to promote the dissolution of the enzyme protein, and 0.015M EDTA is used to chelate metal ions to prevent potential inhibition or interference of metal ions on enzyme activity. Add the dried papaya powder to the Tris-HCl buffer solution at a ratio of 1g:7mL, place it in a low temperature environment of 4°C, and slowly stir it on a magnetic stirrer for 5h to ensure that the enzyme protein is fully dissolved in the buffer solution. Transfer the extract to a high-speed refrigerated centrifuge, centrifuge it at 4°C and 11000rpm for 25min, separate the supernatant, add ammonium sulfate powder to the supernatant, stir it while adding, and gradually increase its saturation to 50%, let it stand at 4°C for 3h to promote the precipitation of elastase, and then centrifuge it again at a speed of 11000rpm and a temperature of 4°C for 25min, collect the precipitate, and obtain a plant-derived protease;
[0081] S4. The zirconium chloride was dissolved in N,N-dimethylformamide and stirred at room temperature for 1.5h to prepare a zirconium chloride solution having a concentration of 0.09M;
[0082] S5. The terephthalic acid was dissolved in N, N-dimethylformamide and stirred at room temperature for 1.5h to prepare a terephthalic acid solution having a concentration of 0.09M;
[0083] S6. The zirconium chloride solution and the terephthalic acid solution were mixed in a polytetrafluoroethylene-lined reactor at a molar ratio of 1:1, and acetic acid was added as a regulator. The molar ratio of acetic acid to zirconium chloride was 1.8:1 to control the growth rate and particle size of MOF. After the reactor was sealed, it was placed in an oven and reacted at 110°C for 11 hours. During the reaction, the metal ions and the organic ligands underwent a coordination reaction in a high temperature and high pressure solvent environment to obtain MOF particles with a particle size of 3 nm.
[0084] S7. The MOF particles were dispersed in a toluene solution, 3-aminopropyltriethoxysilane was added, the mass ratio of 3-aminopropyltriethoxysilane to MOF particles was 9:100, and the mixture was stirred and reacted at 75°C for 8 hours under nitrogen protection to modify the surface of the MOF particles to enhance the binding ability of the MOF particles with the enzyme. After the reaction, the surface-modified MOF particles were collected by centrifugation, washed three times with toluene and ethanol respectively to remove the unreacted silane coupling agent, and then dried in a vacuum drying oven to obtain functionalized MOF particles.
[0085] S8. Dissolve 25 g of collagen hydrolase and 23 g of plant-derived protease in a phosphate buffer solution at pH = 7.5, add 325 g of functionalized MOF microparticles, and react at room temperature with stirring for 18 h to load the enzyme onto the MOF microparticles by physical adsorption or chemical bonding to obtain metal organic framework enzyme-loaded microparticles;
[0086] S9. Mix 13 g of collagen hydrolase, 11 g of plant-derived protease and 20 g of metal organic framework enzyme-loaded microparticles to obtain reagent B.
[0087] Preparation Example 6: A method for preparing reagent B, comprising the following steps:
[0088] S1. Wash the pig gastric mucosal tissue, remove the fat, blood and other impurities on the surface and cut it into small pieces. Put 20 mL of the pretreated gastric mucosal tissue into 100 mL of phosphate buffer solution with pH = 7.5 and containing 0.5 M NaCl. At 10°C, use a homogenizer to homogenize the tissue to break the cells and release the enzyme. Then, stir and extract the homogenate at 10°C for 6 hours to allow the collagenase to be fully dissolved in the extraction buffer. Then, centrifuge the extracted homogenate at 6000 rpm for 30 minutes to remove tissue residues and insoluble matter to obtain a supernatant containing collagenase. Add solid ammonium sulfate to the obtained supernatant to make the saturation of ammonium sulfate reach 60%. Let it stand at 4°C for 4 hours to precipitate the collagenase. Then, collect the precipitate by centrifugation to obtain collagenase.
[0089] S2. Picking ripe and fresh papaya, removing the dirt, impurities and soft and rotten parts on the surface, washing with clean water and draining, peeling and core-removing the papaya, cutting into small pieces, and freezing the cut papaya pieces in liquid nitrogen for 60 minutes. This step can instantly freeze the papaya cells, destroy the cell structure, facilitate the release of subsequent enzymes, and help reduce the activity loss of the enzymes before extraction. The frozen papaya pieces are placed in a vacuum freeze dryer and dried at -40°C and a vacuum degree of about 0.08MPa for 48 hours until the material is completely dehydrated and becomes a loose and fragile dry block, which is convenient for subsequent grinding into powder;
[0090] S3. Add 0.2M NaCl and 0.02M EDTA to a Tris-HCl buffer solution of pH=8.0, wherein 0.2M NaCl is used to maintain a suitable ionic strength and promote the dissolution of the enzyme protein, and 0.02M EDTA is used to chelate metal ions to prevent potential inhibition or interference of metal ions on enzyme activity. Add the dried papaya powder to the Tris-HCl buffer solution at a ratio of 1g:10mL, place it in a low temperature environment of 4°C, and slowly stir it on a magnetic stirrer for 6h to ensure that the enzyme protein is fully dissolved in the buffer solution. Transfer the extract to a high-speed refrigerated centrifuge, centrifuge it at 4°C and 12000rpm for 30min, separate the supernatant, add ammonium sulfate powder to the supernatant, stir it while adding, and gradually increase its saturation to 60%, let it stand at 4°C for 4h to promote the precipitation of elastase, and then centrifuge it again at a speed of 12000rpm and a temperature of 4°C for 30min, collect the precipitate, and obtain a plant-derived protease;
[0091] S4. The zirconium chloride was dissolved in N,N-dimethylformamide and stirred at room temperature for 2h to prepare a zirconium chloride solution with a concentration of 0.1M;
[0092] S5. The terephthalic acid was dissolved in N, N-dimethylformamide and stirred at room temperature for 1-2h to prepare a terephthalic acid solution having a concentration of 0.1M;
[0093] S6. The zirconium chloride solution and the terephthalic acid solution are mixed in a polytetrafluoroethylene-lined reactor at a molar ratio of 1:1, and acetic acid is added as a regulator. The molar ratio of acetic acid to zirconium chloride is 2:1 to control the growth rate and particle size of MOF. After the reactor is sealed, it is placed in an oven and reacted at 120°C for 12 hours. During the reaction, the metal ions and the organic ligands undergo coordination reaction in a high temperature and high pressure solvent environment to obtain MOF particles with a particle size of 5 nm.
[0094] S7. The MOF particles were dispersed in a toluene solution, 3-aminopropyltriethoxysilane was added, and the mass ratio of 3-aminopropyltriethoxysilane to MOF particles was 10:100. The mixture was stirred and reacted at 80° C. for 12 h under nitrogen protection to modify the surface of the MOF particles so as to enhance the binding ability of the MOF particles with the enzyme. After the reaction, the surface-modified MOF particles were collected by centrifugation, washed three times with toluene and ethanol respectively to remove the unreacted silane coupling agent, and then dried in a vacuum drying oven to obtain functionalized MOF particles.
[0095] S8. Dissolve 30 g of collagen hydrolase and 25 g of plant-derived protease in a phosphate buffer solution at pH = 8, add 350 g of functionalized MOF microparticles, and react at room temperature with stirring for 24 h to load the enzyme onto the MOF microparticles by physical adsorption or chemical bonding to obtain metal organic framework enzyme-loaded microparticles;
[0096] S9. Mix 15 g of collagen hydrolase, 12 g of plant-derived protease and 22 g of metal organic framework enzyme-loaded microparticles to obtain reagent B.
[0097] Preparation Example 7: A method for preparing reagent C, comprising the following steps:
[0098] S1. placing phytosterols with a purity of 95% in a vacuum oven, drying at 50°C and a vacuum degree of 0.08 MPa for 2 h to remove moisture and a small amount of volatile impurities, grinding the dried phytosterols into fine powder, and passing through an 80-mesh sieve to better disperse in the reaction system to obtain phytosterols;
[0099] S2. Select chitosan with a deacetylation degree of 80% and a molecular weight of 60 kDa, use glycidyl trimethyl ammonium chloride as a quaternizing agent, disperse chitosan in an isopropanol-water mixed solvent, wherein the volume ratio of isopropanol to water in the isopropanol-water mixed solvent is 1:1, add sodium hydroxide to adjust the pH to 10, slowly dropwise add a 20% glycidyl trimethyl ammonium chloride solution, stir and react at 60°C for 6 hours, after the reaction is completed, wash with ethanol 3 times to remove unreacted reagents and salts to obtain chitosan quaternary ammonium salt, dissolve the prepared chitosan quaternary ammonium salt in deionized water to prepare a solution with a mass fraction of 5%, filter through a 0.22 μm filter membrane before use to remove possible insoluble impurities to obtain a chitosan quaternary ammonium salt solution;
[0100] S3. soaking wood pulp in a buffer solution containing TEMPO, sodium bromide and sodium hypochlorite, the pH of the buffer solution is 10, reacting at room temperature in the dark for 2 hours, stirring continuously during the reaction, washing with deionized water to neutrality after the reaction, obtaining oxidized cellulose with carboxyl groups on the surface, and then dispersing the oxidized cellulose in water, using an ultrasonic cell disruptor at a power of 400W for 30 minutes to depolymerize the cellulose into nanometer size, obtaining an amphiphilic nanocellulose suspension, adjusting the solid content to 2%, and centrifuging at a speed of 8000rpm for 10 minutes to remove large particle impurities that are not completely depolymerized, and obtaining amphiphilic nanocellulose;
[0101] S4. In a three-necked flask equipped with a mechanical stirrer, a thermometer and a condenser, deionized water is added, the deionized water accounts for 40% of the total mass of the emulsion, the temperature is raised to 40°C, stirred at 300rpm, and the phytosterol powder is slowly added dropwise, and an emulsifier is added at the same time, the emulsifier is Tween-80, and the amount of the emulsifier is 10% of the mass of the phytosterols. Stirring is continued for 30 minutes to form a primary emulsion of phytosterols, the hydrophilic group of the emulsifier is toward the water phase, and the lipophilic group wraps the phytosterol particles, so that it is initially dispersed in the water phase;
[0102] S5. The chitosan quaternary ammonium salt solution is slowly added dropwise to the primary emulsion of phytosterols. The dropping time is controlled within 20 minutes. During this period, the temperature is raised to 60°C, the stirring speed is increased to 500 rpm, and the reaction is carried out for 1 hour to allow the chitosan quaternary ammonium salt and the phytosterols to interact to a certain extent, such as electrostatic adsorption, hydrogen bonding, etc., to enhance the stability and functionality of the emulsion. Subsequently, the amphiphilic nanocellulose suspension is added dropwise to the reaction system. After the dropwise addition is completed, the stirring reaction is continued at 70°C for 2 hours to promote the uniform dispersion of the nanocellulose and further compound with other components in the emulsion to form a bio-based emulsion with a stable structure. The amphiphilicity of the nanocellulose enables it to interact with the chitosan quaternary ammonium salt in the aqueous phase and to connect with the phytosterol particles through the hydrophobic region, playing the role of a bridge and reinforcing the structure. The mass ratio of phytosterols, chitosan quaternary ammonium salt solution and amphiphilic nanocellulose is 3:80:2 to obtain reagent C.
[0103] Preparation Example 8: A method for preparing reagent C, comprising the following steps:
[0104] S1. The phytosterol with a purity of 96% was placed in a vacuum oven and dried at 55°C and a vacuum degree of 0.085 MPa for 2.5 hours to remove moisture and a small amount of volatile impurities. The dried phytosterol was ground into fine powder and passed through a 90-mesh sieve to better disperse it in the reaction system to obtain phytosterol;
[0105] S2. Select chitosan with a deacetylation degree of 85% and a molecular weight of 70 kDa, use glycidyl trimethyl ammonium chloride as a quaternizing agent, disperse chitosan in an isopropanol-water mixed solvent, wherein the volume ratio of isopropanol to water in the isopropanol-water mixed solvent is 1:1, add sodium hydroxide to adjust the pH to 10.5, slowly drop a 25% glycidyl trimethyl ammonium chloride solution, stir and react at 65°C for 7 hours, after the reaction is completed, wash with ethanol 3 times to remove unreacted reagents and salts to obtain chitosan quaternary ammonium salt, dissolve the prepared chitosan quaternary ammonium salt in deionized water to prepare a solution with a mass fraction of 8%, filter through a 0.35 μm filter membrane before use to remove possible insoluble impurities to obtain a chitosan quaternary ammonium salt solution;
[0106] S3. Soaking wood pulp in a buffer solution containing TEMPO, sodium bromide and sodium hypochlorite, the pH of the buffer solution is 10.3, reacting at room temperature in the dark for 2.5 hours, stirring continuously during the reaction, washing with deionized water to neutrality after the reaction, obtaining oxidized cellulose with carboxyl groups on the surface, and then dispersing the oxidized cellulose in water, using an ultrasonic cell disruptor at a power of 500 W for 50 minutes to depolymerize the cellulose into nanometer size, obtaining an amphiphilic nanocellulose suspension, the solid content of which is adjusted to 2.5%, and centrifuging at a speed of 9000 rpm for 13 minutes to remove large particle impurities that are not completely depolymerized, and obtaining amphiphilic nanocellulose;
[0107] S4. In a three-necked flask equipped with a mechanical stirrer, a thermometer and a condenser, deionized water is added, the deionized water accounts for 45% of the total mass of the emulsion, the temperature is raised to 45°C, stirred at 350rpm, and the phytosterol powder is slowly added dropwise. At the same time, an emulsifier is added, the emulsifier is Tween-80, and the amount of the emulsifier is 15% of the mass of the phytosterol. Stirring is continued for 35 minutes to form a primary emulsion of phytosterols. The hydrophilic group of the emulsifier faces the water phase, and the lipophilic group wraps the phytosterol particles to make them initially dispersed in the water phase;
[0108] S5. The chitosan quaternary ammonium salt solution is slowly added dropwise to the primary emulsion of phytosterols. The dropping time is controlled within 25 minutes. During this period, the temperature is raised to 65°C, the stirring speed is increased to 550rpm, and the reaction is carried out for 1.5 hours to allow the chitosan quaternary ammonium salt and the phytosterols to interact to a certain extent, such as electrostatic adsorption, hydrogen bonding, etc., to enhance the stability and functionality of the emulsion. Subsequently, the amphiphilic nanocellulose suspension is added dropwise to the reaction system. After the dropwise addition is completed, the stirring reaction is continued at 75°C for 2.5 hours to promote the uniform dispersion of the nanocellulose and further compound with other components in the emulsion to form a bio-based emulsion with a stable structure. The amphiphilicity of the nanocellulose enables it to interact with the chitosan quaternary ammonium salt in the aqueous phase and to connect with the phytosterol particles through the hydrophobic region, playing the role of a bridge and reinforcing the structure. The mass ratio of phytosterols, chitosan quaternary ammonium salt solution and amphiphilic nanocellulose is 4:83:2.5, and reagent C is obtained.
[0109] Preparation Example 9: A method for preparing reagent C, comprising the following steps:
[0110] S1. The phytosterol with a purity of 98% was placed in a vacuum oven and dried at 60°C and a vacuum degree of 0.09 MPa for 3 hours to remove moisture and a small amount of volatile impurities. The dried phytosterol was ground into fine powder and passed through a 100-mesh sieve to better disperse it in the reaction system to obtain phytosterol;
[0111] S2. Select chitosan with a deacetylation degree of 90% and a molecular weight of 80 kDa, use glycidyl trimethyl ammonium chloride as a quaternizing agent, disperse chitosan in an isopropanol-water mixed solvent, wherein the volume ratio of isopropanol to water in the isopropanol-water mixed solvent is 1:1, add sodium hydroxide to adjust the pH to 11, slowly dropwise add a 30% glycidyl trimethyl ammonium chloride solution, stir and react at 70°C for 8h, after the reaction is completed, wash with ethanol 3 times to remove unreacted reagents and salts to obtain chitosan quaternary ammonium salt, dissolve the prepared chitosan quaternary ammonium salt in deionized water to prepare a solution with a mass fraction of 10%, filter through a 0.45 μm filter membrane before use to remove possible insoluble impurities to obtain a chitosan quaternary ammonium salt solution;
[0112] S3. Soaking wood pulp in a buffer solution containing TEMPO, sodium bromide and sodium hypochlorite, wherein the pH of the buffer solution is 10.5, and reacting at room temperature in the dark for 3 hours with continuous stirring. After the reaction is completed, washing with deionized water until neutral to obtain oxidized cellulose with carboxyl groups on the surface, and then dispersing the oxidized cellulose in water, using an ultrasonic cell disruptor at a power of 600 W for 60 minutes to depolymerize the cellulose into nanometer size, obtaining an amphiphilic nanocellulose suspension, wherein the solid content is adjusted to 3%, and centrifuging at a speed of 10,000 rpm for 15 minutes to remove large particle impurities that are not completely depolymerized, and obtaining an amphiphilic nanocellulose suspension;
[0113] S4. In a three-necked flask equipped with a mechanical stirrer, a thermometer and a condenser, deionized water is added, the deionized water accounts for 50% of the total mass of the emulsion, the temperature is raised to 50°C, stirred at 400rpm, and the phytosterol powder is slowly added dropwise, and an emulsifier is added at the same time, the emulsifier is Tween-80, and the amount of the emulsifier is 20% of the mass of the phytosterols. Stirring is continued for 40min to form a primary emulsion of phytosterols, the hydrophilic group of the emulsifier is toward the water phase, and the lipophilic group wraps the phytosterol particles, so that it is initially dispersed in the water phase;
[0114] S5. The chitosan quaternary ammonium salt solution is slowly added dropwise to the primary emulsion of phytosterols. The dropping time is controlled within 30 minutes. During this period, the temperature is raised to 70°C, the stirring speed is increased to 600 rpm, and the reaction is carried out for 2 hours to allow the chitosan quaternary ammonium salt and the phytosterols to interact to a certain extent, such as electrostatic adsorption, hydrogen bonding, etc., to enhance the stability and functionality of the emulsion. Subsequently, the amphiphilic nanocellulose suspension is added dropwise to the reaction system. After the dropwise addition is completed, the stirring reaction is continued at 80°C for 3 hours to promote the uniform dispersion of the nanocellulose and further compound with other components in the emulsion to form a bio-based emulsion with a stable structure. The amphiphilicity of the nanocellulose enables it to interact with the chitosan quaternary ammonium salt in the aqueous phase and to connect with the phytosterol particles through the hydrophobic region, playing the role of a bridge and reinforcing the structure. The mass ratio of phytosterols, chitosan quaternary ammonium salt solution and amphiphilic nanocellulose is 5:85:3, and reagent C is obtained.
[0115] Embodiment 1: A green and environmentally friendly leather softening method, comprising the following steps:
[0116] S1. Pretreatment: Place the rawhide in a 25°C warm water bath and stir for 30 minutes to wash away impurities and blood on the surface of the rawhide, then subject it to 20kHz, 400W ultrasonic vibration for 15 minutes to remove impurities and open pores, and then place it in a 2.45GHz, 600W microwave cavity for 10 minutes to accelerate the temperature rise to promote fiber expansion and lay the foundation for softening. After draining, use the reagent A obtained in Preparation Example 1 to adjust the pH to 7.5 to neutralize the natural acid, activate the subsequent reaction, create a suitable charge and osmotic pressure environment for the enzyme molecules, and promote subsequent efficient attachment and penetration. This mild treatment can avoid damage to the leather structure, wherein the amount ratio of rawhide to water is 10g:100mL, and a leather crude product 1 is obtained;
[0117] S2. Softening: The crude leather product 1 is immersed in a buffer solution containing 3% of the reagent B obtained in Preparation Example 4, and shaken at 40°C, pH = 7, and 80 rpm for 2 hours, with precise temperature control to maintain enzyme activity and shaking to promote uniform enzyme contact, wherein the bath ratio during softening is 1:8, and the buffer solution is disodium hydrogen phosphate-citric acid, to obtain a crude leather product 2;
[0118] S3. Finishing: The leather crude product 2 is bombarded with nitrogen plasma at 50W for 3 minutes to increase the surface activity and make the grafted emulsion stronger. Then it is put into an emulsion containing 8% of the reagent C obtained in Preparation Example 7 with a bath ratio of 1:6. It is tanned at 50°C for 80 minutes. Warmth helps the oil to penetrate and the tanning is evenly distributed. Then it is cured at 45°C for 20 minutes to make the film dense and the color bright and lasting. The emulsion particle size is 80nm and it is stably dispersed. After spraying, it becomes a nano film, which gives the leather waterproof, breathable and antibacterial functions. The source is fully biodegradable and has no ecological burden. The content of emulsifier in the emulsion is 0.5%-0.6%, and a leather product is obtained.
[0119] Embodiment 2: A green and environmentally friendly leather softening method, comprising the following steps:
[0120] S1. Pretreatment: Place the rawhide in a 28°C warm water bath and stir for 30 minutes to wash away impurities and blood on the surface of the rawhide, then subject it to 20kHz, 400W ultrasonic oscillation for 15 minutes to remove impurities and open pores, and then place it in a 2.45GHz, 600W microwave cavity for 10 minutes to accelerate the temperature rise to promote fiber expansion and lay the foundation for softening. After draining, use the reagent A obtained in Preparation Example 2 to adjust the pH to 7.8 to neutralize the natural acid, activate the subsequent reaction, create a suitable charge and osmotic pressure environment for the enzyme molecules, and promote subsequent efficient attachment and penetration. This mild treatment can avoid damage to the leather structure. The amount ratio of rawhide to water is 11g:105mL to obtain a leather crude product 1;
[0121] S2. Softening: The crude leather product 1 is immersed in a buffer solution containing 3.3% of the reagent B obtained in Preparation Example 5, and shaken at 43°C, pH = 7.3, and 90 rpm for 2.5 hours, and the temperature is precisely controlled to maintain the enzyme activity, and the shaking promotes uniform enzyme contact, wherein the bath ratio during softening is 1:8.5, and the buffer solution is disodium hydrogen phosphate-citric acid, to obtain a crude leather product 2;
[0122] S3. Finishing: The leather crude product 2 is bombarded with nitrogen plasma at 50W for 3 minutes to increase the surface activity and make the grafted emulsion stronger. Then it is put into an emulsion containing 9% of the reagent C obtained in Preparation Example 8 with a bath ratio of 1:7. It is tanned at 53°C for 85 minutes. Warmth helps the oil penetration and the tanning is evenly distributed. Then it is cured at 48°C for 20 minutes to make the film dense and the color bright and lasting. The emulsion particle size is 100nm and it is stably dispersed. After spraying, it becomes a nano film, which gives the leather waterproof, breathable and antibacterial functions. The source is fully biodegradable and has no ecological burden. The content of emulsifier in the emulsion is 0.55%, and a leather product is obtained.
[0123] Embodiment 3: A green and environmentally friendly leather softening method, comprising the following steps:
[0124] S1. Pretreatment: Place the rawhide in a 30°C warm water bath and stir for 30 minutes to wash away impurities and blood on the surface of the rawhide, then subject it to 20kHz, 400W ultrasonic oscillation for 15 minutes to remove impurities and open pores, and then place it in a 2.45GHz, 600W microwave cavity for 10 minutes to accelerate the temperature rise to promote fiber expansion and lay the foundation for softening. After draining, use the reagent A obtained in Preparation Example 3 to adjust the pH to 8, neutralize the natural acid, activate the subsequent reaction, create a suitable charge and osmotic pressure environment for the enzyme molecules, and promote subsequent efficient attachment and penetration. This mild treatment can avoid damage to the leather structure, wherein the amount ratio of rawhide to water is 12g:110mL, and a leather crude product 1 is obtained;
[0125] S2. Softening: The crude leather product 1 is immersed in a buffer solution containing 3.5% of the reagent B obtained in Preparation Example 6, and shaken at 45°C, pH = 7.5, and 100 rpm for 3 hours, and the temperature is precisely controlled to maintain the enzyme activity, and the shaking promotes uniform contact of the enzyme, wherein the bath ratio during softening is 1:9, and the buffer solution is disodium hydrogen phosphate-citric acid, to obtain a crude leather product 2;
[0126] S3. Finishing: The leather crude product 2 is bombarded with nitrogen plasma at 50W for 3 minutes to enhance the surface activity and make the grafted emulsion stronger. Then, it is put into an emulsion containing 10% of the reagent C obtained in Preparation Example 9 with a bath ratio of 1:8. It is tanned at 55°C for 90 minutes. Warmth helps the oil to penetrate and the tanning is evenly distributed. Then, it is cured at 50°C for 20 minutes to make the film dense and the color bright and lasting. The emulsion particle size is 120nm and it is stably dispersed. After spraying, it becomes a nano film, which gives the leather waterproof, breathable and antibacterial functions. The source is fully biodegradable and has no ecological burden. The content of emulsifier in the emulsion is 0.6%, and a leather product is obtained.
[0127] Comparative Example 1:
[0128] Compared with Example 1, this comparative example did not perform pretreatment during the leather softening process, and the remaining steps and parameters were the same, which will not be repeated in this comparative example. Finally, a leather product was obtained.
[0129] Comparative Example 2:
[0130] Compared with Example 1, this comparative example only replaces "reagent B obtained in Preparation Example 4" with "a mixture of equal amounts of collagen hydrolase and plant-derived protease", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a leather finished product is obtained.
[0131] Comparative Example 3:
[0132] Compared with Example 1, this comparative example only replaces "reagent B obtained in Preparation Example 4" with "a mixture obtained by mixing 18g collagen hydrolase, 10g plant-derived protease and 10g metal organic framework enzyme-loaded microparticles", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a leather finished product is obtained.
[0133] Performance test: The leather products obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to the following performance tests.
[0134] Softness: Use LLY-01 leather softness tester to cut the leather sample into specified size, measure the thickness and compression deformation of the leather under a certain pressure, and calculate the softness value. The larger the value, the softer the leather, and the unit is mm.
[0135] Tensile strength: According to GB / T3923.1-2013 “Tensile properties of textile fabrics Part 1: Determination of breaking strength and elongation at break (strip method)”, use an electronic universal testing machine to conduct a tensile test on the leather sample until the sample breaks, and record the maximum tensile force at break, which is the tensile strength in MPa.
[0136] Tear strength: According to QB / T1131-1991 "Determination of tear force of leather: double-sided tearing method", a specific shape of incision is cut on the leather sample, and then a tensile testing machine is used to perform a tear test, and the force required to tear the incision is measured as the tear strength, the unit is N / mm;
[0137] Waterproof performance: Use the hydrostatic pressure method to fix the leather sample on the tester and gradually increase the water pressure until water penetrates from the leather surface. Record the water pressure value at this time as the waterproof performance index. The larger the water pressure value, the better the waterproof performance. The unit is kPa.
[0138] Air permeability: Refer to GB / T5453-1997 "Determination of air permeability of textile fabrics" and use a fabric air permeability meter to measure the air permeability of leather samples under a certain pressure difference. The greater the air permeability, the better the air permeability, and the unit is mm / s.
[0139] Antibacterial performance: Referring to GB / T20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", the leather sample is contacted with a certain concentration of bacterial suspension, and after oscillation culture under specific conditions for a certain period of time, the bacterial reduction rate is measured to evaluate the antibacterial performance. The higher the bacterial reduction rate, the stronger the antibacterial performance, the unit is %.
[0140] The results are shown in Table 1 below:
[0141] Table 1 Performance test results statistics
[0142] project Softness Tensile Strength Tear strength Waterproof Breathable performance Bacteria reduction rate Example 1 3.5 12.8 28.5 3.2 150 95 Example 2 3.8 13.2 30.2 3.5 165 97 Example 3 4.2 13.5 32.8 3.8 180 98 Comparative Example 1 2.2 10.5 22.3 2.5 120 75 Comparative Example 2 2.8 11.2 24.6 2.8 130 80 Comparative Example 3 3.1 11.9 26.1 2.9 142 91
[0143] Data Analysis:
[0144] As can be seen from Table 1, the softness values of Examples 1-3 reached 3.5mm, 3.8mm and 4.2mm respectively, showing a good soft texture, which is due to the unique softening process, especially the precise action of the composite enzyme preparation in reagent B. The metal organic framework-loaded enzyme particles can release enzymes according to the internal stress of the leather, gently and efficiently hydrolyze the leather fibers, avoid excessive damage, and cooperate with plant-derived elastase and targeted collagenase to loosen the fiber structure moderately, giving the leather excellent softness; while Comparative Example 1 was not pretreated, the fiber was not stretched enough, and Comparative Examples 2 and 3 lacked the precise enzyme controlled release system of reagent B, the softening effect was limited, and the softness was significantly low.
[0145] The tensile strength of Examples 1-3 is stably maintained at a high level, between 12.8MPa and 13.5MPa, which is attributed to many factors. On the one hand, the pretreatment stage is ultrasonic and microwave synergistic treatment, which does not destroy the main structure of the fiber when cleaning impurities and opening pores, laying the foundation for subsequent processing; on the other hand, the enzymatic hydrolysis of reagent B is moderate, which does not excessively weaken the fiber strength, and the nanocellulose in reagent C in the finishing stage effectively enhances the overall structure of the leather. In contrast, in the comparative examples, comparative example 1 lacks pretreatment, the fiber arrangement is disordered, and it is easy to break under stress, and the tensile strength is only 10.5MPa; the tensile strength of comparative examples 2 and 3 is lower than that of the examples due to unreasonable enzyme preparation combinations, damaged fibers or poor bonding.
[0146] The tear strength of Examples 1-3 is relatively high. The pretreatment optimizes the basic properties of the fiber, the precise enzyme action during softening maintains the fiber continuity, and the emulsion components penetrate and fill to form a stable structure during finishing. However, due to the lack of pretreatment, the comparative example 1 has many internal defects in the leather and the tear strength is as low as 22.3N / mm. Due to the imperfect enzyme system, the adhesion between fibers in comparative examples 2 and 3 is weak, and the tear strength is far less than that of the embodiments.
[0147] Examples 1-3 have good water resistance, with the hydrostatic pressure value rising from 3.2 kPa to 3.8 kPa. This is due to the emulsion of Reagent C in the finishing stage. Phytosterols and nanocellulose synergistically construct a hydrophobic barrier, and chitosan quaternary ammonium salt assists in stabilizing the emulsion film and enhancing water resistance. Comparative Example 1 was not pretreated, resulting in large leather pores and strong water absorption, with a water resistance of only 2.5 kPa.
[0148] Examples 1-3 have good air permeability, with an air permeability of 150 mm / s to 180 mm / s, taking into account both waterproofness and breathability and comfort. The emulsion of reagent C forms a uniform film with nanoscale pores and does not hinder water vapor exchange. The lack of pretreatment in comparative example 1 causes abnormal density of the leather structure and obstructed air permeability, which is only 120 mm / s.
[0149] The antibacterial rates of Examples 1-3 are as high as 95%-98%. The chitosan quaternary ammonium salt in reagent C plays a key antibacterial role, and its positive charge interacts with the bacterial cell membrane to destroy the bacterial structure; Comparative Example 1 retains a large number of impurity microorganisms without pretreatment, and the subsequent process adaptation is poor, with an antibacterial rate of 75%.
[0150] In summary, the embodiments of the present invention, through a complete and finely designed pretreatment, softening and finishing process, combined with a compound enzyme preparation and a bio-based emulsion, demonstrate a high degree of balance and excellent quality in key properties of leather products such as softness, toughness, waterproofness, breathability and antibacterial properties, which effectively highlights the great advantages of innovative processes and materials.
[0151] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0152] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A green and environmentally friendly leather softening method, characterized in that: The following steps are involved: Step S1. Pretreatment: pretreating the leather with reagent A to obtain a crude leather product 1; Step S2. Softening: Softening the crude leather product 1 with reagent B to obtain the crude leather product 2; Step S3. Finishing: using reagent C to finish the leather crude product 2 to obtain a leather finished product; In step S1, the reagent A is a mixed solution of sodium bicarbonate and magnesium sulfate; The reagent B in step S2 is a complex enzyme preparation; The complex enzyme preparation is obtained by mixing collagen hydrolase, plant-derived protease and metal organic framework enzyme-carrying microparticles; The reagent C in step S3 is a bio-based emulsion.
2. The green and environmentally friendly leather softening method according to claim 1, characterized in that: The pre-processing process in step S1 is as follows: Place the raw hide in a 25-30°C warm water bath, stir for 30 minutes, and then subject it to 20kHz, 400W ultrasonic vibration for 15 minutes, and then place it in a 2.45GHz, 600W microwave cavity for 10 minutes, drain and adjust the pH to 7.5-8 with reagent A; The usage ratio of the raw hide to water is 10-12 g:100-110 mL.
3. The green and environmentally friendly leather softening method according to claim 1, characterized in that: The preparation process of reagent A in step S1 is as follows: Mixing a 1% sodium bicarbonate solution, a 0.5% glucose solution and a 0.3% magnesium sulfate solution to obtain reagent A; The volume ratio of the sodium bicarbonate solution, the glucose solution and the magnesium sulfate solution is 55-58:28-30:12-16.
4. The green and environmentally friendly leather softening method according to claim 1, characterized in that: The softening process in step S2 is as follows: The crude leather product 1 is immersed in a buffer solution containing 3%-3.5% reagent B, and shaken at 40-45°C, pH=7-7.5, and 80-100 rpm for 2-3 hours; The bath ratio during softening is 1:8-9, and the buffer solution is disodium hydrogen phosphate-citric acid.
5. The green and environmentally friendly leather softening method according to claim 1, characterized in that: The collagenase in the reagent B is prepared from pig gastric mucosal tissue; The plant-derived protease in the reagent B is prepared from papaya tissue.
6. The green and environmentally friendly leather softening method according to claim 1, characterized in that: The metal organic framework enzyme-carrying microparticles in the reagent B are prepared from zirconium chloride, and the particle size of the metal organic framework in the metal organic framework enzyme-carrying microparticles is 2-5 nm.
7. The green and environmentally friendly leather softening method according to claim 1, characterized in that: The mass ratio of collagen hydrolase, plant-derived protease and metal organic framework enzyme-loaded microparticles in the reagent B is 10-15:10-12:18-22 g.
8. The green and environmentally friendly leather softening method according to claim 1, characterized in that: The retouching process in step S3 is as follows: The leather crude product 2 was bombarded with nitrogen plasma at 50W for 3 minutes, then put into reagent C with a bath ratio of 1:6-8, tanned at 50-55°C for 80-90 minutes, and then cured at 45-50°C for 20 minutes.
9. The green and environmentally friendly leather softening method according to claim 1, characterized in that: The particle size of the bio-based emulsion in step S3 is 80-120 nm, and the deionized water in the bio-based emulsion accounts for 40%-50% of the total mass.
10. The green and environmentally friendly leather softening method according to claim 1, characterized in that: The mass ratio of phytosterol, chitosan quaternary ammonium salt solution and amphiphilic nanocellulose in the reagent C is 3-5:80-85:2-3.
Citation Information
Patent Citations
Leather tanning agent
CN110184396A
Chitosan emulsion material of immobilized enzyme and application of chitosan emulsion material in synthesis of phytosterol acetate through catalytic esterification reaction
CN116179530A
Preparation and application of Pickering multiple emulsion with stable phytosterol / chitosan composite particles
CN117084979A
Preparation method of environment-friendly anti-cracking leather
CN117646090A
Tanning unhairing method based on keratinase and nano tourmaline powder improved compound enzyme preparation
CN118166169A